Lugares de reunión, boni homines y presbíteros en Valdevimbre y Ardón en la Alta Edad Media - Fernando Luis Corral (Medievalista)
The aim of this article is to better understand some features of the social and political development of the peasant communities located at the area of Ardón and Valdevimbre (south of the city of León, Spain) in the Early Middle Ages. Leonese charters from 10th.-11th. centuries shows us the opportunity to know some of the local elite members, if we pay attention to repeated mentions of boni homines (good men) and local priests who appear on these charters. This fact reports us about the increasing social inequality produced inside these peasant communities.We will also explore changes in location of meeting places chosen to solve conflicts between community members and the ones of some ecclesiastical institutions and aristocracy as a way to better know the political side of the relationship between the mentioned peasant communities and those power elites and, through them, with the Astur-leonese central power.